(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines digital media’s effect on language evolution. The current stage of electronic learning of foreign languages is characterized by the development of Internet technologies and mobile applications. Examples of effective methods of teaching foreign languages using computers are given, facilitating the learning of all basic types of speech activity: reading, writing, speaking and listening.